Changes between Version 6 and Version 7 of u/johannjc/scratchpad4
- Timestamp:
- 09/30/15 17:03:58 (9 years ago)
Legend:
- Unmodified
- Added
- Removed
- Modified
-
u/johannjc/scratchpad4
v6 v7 59 59 we get expressions for 60 60 61 $A = \frac{1}{\Delta t}$62 63 61 $B_j = \frac{\kappa_\parallel \left ( \phi-\psi\lambda \right )}{\lambda+1} \partial_i n b_i b_j $ 64 62 … … 71 69 We then need expressions for 72 70 73 $ \partial_t T = A \left ( T'_0 - T_0 \right )$71 $ \partial_t T = \frac{ T'_0 - T_0}{\Delta t}$ 74 72 75 73 $ \partial_j T^{\lambda+1} = \frac{T^{\lambda+1}_{\hat{j}} - T^{\lambda+1}_{-\hat{j}}}{2 \Delta x}$ … … 91 89 $\alpha_{\pm j} = \pm C_jT^\lambda_{\pm \hat{j}} + \frac{E_{jj}}{\Delta x^2}T_{\pm \hat{j}}^\lambda$ 92 90 93 $\alpha_{\pm i \pm j} = \pm \pm \frac{E_{ij}}{4 \Delta x^2}T^\lambda_{\pm \hat{i} \pm \hat{j}}$91 $\alpha_{\pm i, \pm j} = \pm \pm \frac{E_{ij}}{4 \Delta x^2}T^\lambda_{\pm \hat{i} \pm \hat{j}}$ 94 92 93 $\beta = -\frac{T_0}{\Delta t} \pm \frac{B_j}{2 \Delta x} T^{\lambda+1}_{\pm \hat{j}} \pm \pm \frac{D_{ij}}{4 \Delta x^2} T^{lambda+1}_{\pm \hat{i} \pm \hat{j}}\left ( 1 - \delta_{ij} \right ) + \frac{D_{jj}}{\Delta x^2} T^{lambda+1}_{\pm \hat{j}} - 2 \frac{D_{jj}}{\Delta x^2}T^{\lambda+1}_0$